From the EU Membership to the Sanctions Against Russia: Factors Behind the Collapse of Estonian Transit Sector. Issue 1 (1st February 2020) - Veebel, Viljar
ABSTRACT: The article aims to investigate the main factors behind changes in the transit flows in Estonian transit sector: first the European integration, second relations with Russia, third the changes in infrastructure, and fourth the changes in trade flows. However, the European dimension appears also in the second, third, and fourth categories, as trade relations with Russia, infrastructural developments, and general trade flows depend on European policy preferences and developments. The importance of the current study is even higher in light of the expected construction of the Rail Baltic railway line, which adds significantly to infrastructural capabilities, but on the other hand also needs growing volumes of trade to be economically sustainable. Additionally, political risks need to be assessed, as growing transit flows related to Russia, which may be beneficial in economic terms, will lead to growing risks to impact or be manipulated by the Russian side, to trade economic benefits for political compromises.